Corelasional Personality (Openness, Conscientiousness, Extraversion, Agreeableness, Neuroticism) and Intention to Act with Responsibility Environmental Behaviour - Sugiarti, Cucu (Jurnal Politikom Indonesiana, 2019)
The objective of the research is to study the relationship personality (openness, conscientiousness, extraversion, agreeableness, neuroticism) and Intention to act with responsibility environment behaviour. It was a quantitative research with an study corelational methode conducted in high school in Bekasi in 2019. The data were collected through questioner. The data analysis and interpretation indicate that 1. There is a positive relationship between personality with responsible environmental behavior. 2. There is a positive relationship between personality with the intention to act. 3. There is a positive relationship between personality, openness with the intention to act. 4. There is a positive relationship between personality, conscientiousness with intention to act. 5. There is a positive relationship between personality, extraversion with the intention to act. 6. There is a positive relationship between personality, agreeableness with the intention to act. 7. There is a positive relationship between personality, neuroticism with the Intention to act. 8. There is a positive relationship between the intention to act with responsible environmental behavior. Keyword: Personality, Openness, Conscientiousness, Extraversion, Agreeableness, Neuroticism, Intention to act, Responsibility Environment Behaviour.